Architectural space of Jan Rybkowski’s Warszawska premiera and Aleksander Ford’s Młodość Chopina. The film vision of 19th-century cities in the times of socialist realism - Kurpiewski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Two Polish historical films set in 19th-century cities were created. The paper analyzes film images of Warsaw, Paris and Vienna. For the needs of Warszawska premiera [Warsaw Première] and especially Młodość Chopina [Youth of Chopin] impressive sets of 19th-century cities were built in an atelier in Łódź. The author presents the main architectural principles behind these visions and points to the problems faced by the artists who wanted to create a credible and convincing illusion of the past. The films of socialist realism are today a peculiar souvenir of the Stalinist culture with its brazen propaganda message. It is, however, worth noting that the staging and decorations in the films depicting the past were created with great historical accuracy and some of the solutions applied during the production of Warsaw Première and Youth of Chopin were a great hint for later films of a similar character.